ECG Acquisition and Automated Remote Processing - Gupta, Rajarshi; Mitra, Madhuchhanda; Bera, Jitendranath; SpringerLink (Online service) (New Delhi : Springer India : Imprint: Springer, 2014)
The book is focused on the area of remote processing of ECG in the context of telecardiology, an emerging area in the field of Biomedical Engineering Application. Considering the poor infrastructure and inadequate numbers of physicians in rural healthcare clinics in India and other developing nations, telemedicine services assume special importance. Telecardiology, a specialized area of telemedicine, is taken up in this book considering the importance of cardiac diseases, which is prevalent in the population under discussion. The main focus of this book is to discuss different aspects of ECG acquisition, its remote transmission and computerized ECG signal analysis for feature extraction. It also discusses ECG compression and application of standalone embedded systems, to develop a cost effective solution of a telecardiology system.
Introduction -- ECG Signal Analysis -- ECG acquisition in a Computer -- ECG Transmission -- ECG Compression -- Challenges and Future Trends in Tele-health Services.
Keywords: Engineering; Cardiology; Biomedical engineering; Engineering; Biomedical Engineering; Signal, Image and Speech Processing; Cardiology